2002
DOI: 10.1128/aem.68.2.519-524.2002
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of Escherichia coli O157:H7 from Rumen Medium Containing Prebiotic Sugars

Abstract: A fed-batch, anaerobic culture system was developed to assess the behavior of Escherichia coli O157:H7 in a rumen-like environment. Fermentation medium consisted of either 50% (vol/vol) raw or sterile rumen fluid and 50% phosphate buffer. Additional rumen fluid was added twice per day, and samples were removed three times per day to simulate the exiting of digesta and microbes from the rumen environment under typical feeding regimens. With both types of medium, anaerobic and enteric bacteria reached 10 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…We show that in raw rumen fluid, growth of E. coli O157:H7 is limited or even suppressed due to the presence of the resident microflora, which exerts a strong barrier effect. These data agree with previous observations made with continuous cultures in 50% diluted rumen fluid (12). Taken together, our results indicate that this barrier effect is due mostly to the observed increase in acetate concentration (acetate represents 65 to 75% of the total VFA mixture) and decrease in pH, resulting from the fermentative activity of the microflora during incubation, but also to other direct or indirect effects not yet identified.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We show that in raw rumen fluid, growth of E. coli O157:H7 is limited or even suppressed due to the presence of the resident microflora, which exerts a strong barrier effect. These data agree with previous observations made with continuous cultures in 50% diluted rumen fluid (12). Taken together, our results indicate that this barrier effect is due mostly to the observed increase in acetate concentration (acetate represents 65 to 75% of the total VFA mixture) and decrease in pH, resulting from the fermentative activity of the microflora during incubation, but also to other direct or indirect effects not yet identified.…”
Section: Discussionsupporting
confidence: 82%
“…Yet it is important to understand better how gut environmental conditions are likely to influence growth or survival of these potentially pathogenic bacteria. Most previous studies were done in sterile laboratory media or in diluted sterile rumen fluid supplemented with purified sugars or Trypticase (12,43,47,56). In this report, we describe original in vitro models for growth of EHEC strains in digestive contents directly harvested from ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this role, the application of the prebiotic: probiotic mixture stopped symptoms in 50% of the symptomatic goats. The prebiotic, Celmanax ™ , contains significant mannose that is known to block FimH-mediated non-O157 STEC adherence to target cells [37] and in vitro studies indicated that it caused a higher magnitude of reduction in colonization for the non-O157 STEC compared with the O157 STEC [3]. The probiotic also produced a decrease in O157 and non-O157 STEC colonization, but the mechanism is not likely related to the presence of mannose.…”
Section: Discussionmentioning
confidence: 99%
“…Another six strains were obtained from the Karch laboratory in Germany. The commensal strains included 31 E. coli reference strains (37) and 8 cattle strains from the culture collections at the University of Wisconsin and University of Nebraska (17). The E. coli O157:H7 portion of the set was designed to represent the genetic and geographic diversity of this serotype in the United States, while the commensal E. coli portion of the set was designed to represent the entire genetic diversity of the species (54).…”
Section: Methodsmentioning
confidence: 99%